Aerobic exercise improves depressive symptoms in the unilateral 6-OHDA-lesioned rat model of Parkinson’s disease - Hannah Loughlin; Jacob Jackson; Chloe Looman; Alayna Starll; Jeremy Goldman; Zhiying Shan; Chunxiu Yu (IBRO Neuroscience Reports, 2024)
Aerobic exercise has been shown to have established benefits on motor function in Parkinson's disease (PD). However, the impact of exercise on depressive symptoms in PD remains unclear. This study aimed to investigate the effects of regular exercise, specifically using a forced running wheel, on both motor performance and the prevalence of depression in a unilateral 6-OHDA-lesioned rat model of PD. The behavioral outcomes of exercise were assessed through the rotarod test (RT), forelimb adjusting step test (FAST), sucrose consumption test (SCT), and novelty sucrose splash test (NSST). Our data revealed evident depressive symptoms in the PD animals, characterized by reduced sucrose consumption in the SCT and diminished exploratory activity in the NSST compared to the naïve control group. Specifically, after 11 weeks of exercise, the PD exercise group demonstrated the most significant improvements in sucrose consumption in the SCT. Additionally, this group exhibited reduced immobility and increased exploratory behavior compared to the PD control group in the NSST. Furthermore, the PD exercise group displayed the greatest improvement in correcting forelimb stepping bias. Our results suggested that a regimen of running wheel exercise enhances motor abilities and mitigates the occurrence of depressive behaviors caused by 6-OHDA dopamine depletion in the PD rat model.